Inward FDI from ASEAN and Its Implication on Malaysian Manufacturing Sector - Mohd Khairul Hisyam, Hassan; Tajul Ariffin, Masron (Jurnal Ekonomi Malaysia, 2011)
Regional FDI or South-South FDI refers to the inflows of FDI from developing countries to another developing country; and it is gaining importance and is growing over time. This can be observed from the increasing amount of outward FDI from developing countries. Without exception, the ASEAN region is also contributing more to outward FDI. While there is an abundance of researches dealing with the inflows of FDI from developed countries into developing countries, in particular into ASEAN countries, less attention has been paid on the FDI from developing countries. As a large chunk of FDI from ASEAN goes into ASEAN neighboring countries, it is the aim of this study to investigate the impact of intra-ASEAN inward FDI on Malaysian manufacturing sector.